Implementasi Konsep Keadilan Restoratif Dalam Penyelesaian Tindak Pidana Anak pada Era Digital di Polres Wajo - Martono; Eva Ayu Ratnasari; Muharawati; Mustari (Yayasan Pengembangan Sumber Daya Insani Lamaddukelleng, 2026)
This study aims to determine the application of the concept of restorative justice in resolving juvenile crimes in the digital era at the Wajo Police Resort; and to determine the factors that influence the application of the concept of restorative justice in resolving juvenile crimes in the digital era at the Wajo Police Resort. The research was conducted at the Wajo Police Resort. The data collection method used was interviews and library research. Data were analyzed qualitatively using deductive and inductive methods and then presented descriptively. Data in the form of direct interviews with related parties and in the form of legal products and reading materials related to the object of study to sharpen and deepen the qualitative analysis. The results of the study indicate that knowing the application of the concept of restorative justice in resolving juvenile crimes in the digital era at the Wajo Police Resort shows that the implementation of restorative justice has been attempted normatively, but empirically has not been running optimally in dealing with the complexity of juvenile crimes in the digital era; The factors influencing the implementation of the restorative justice concept in resolving juvenile crimes in the digital era at the Wajo Police Department include legal substance (regulations and policies), law enforcement officials (legal structure), community and legal culture, facilities, infrastructure, and inter-agency coordination, and the role of the child's family and environment.